Pengaruh Diskon Dan Kepercayaan Konsumen Terhadap Keputusan Pembeli di Aplikasi Shopee. - Siti Rachmatiya Lastmi Dehi; Usman Moonti; Melizubaida Mahmud; Radia Hafid Hafid (State University of Gorontalo, 2023)
This study uses a quantitative approach, with 35 respondents (students) in the Department of Economics Education, Faculty of Economics, Universitas Negeri Gorontalo. The main research instrument is a questionnaire. The data collected are analyzed and tested with multiple linear regression. The results show that there is an effect of discounts and consumer trust on purchasing decisions of Shopee application users in the class of 2018 of Bachelor’s Degree Program in Economic Education, Faculty of Economics, Universitas Negeri Gorontalo. The effect of discounts and consumer trust on purchasing decisions of Shopee application users are 31,1% while the remaining 68,9% is influenced by variables that are not examined.